Analyses of Archival Cartographic Materials for Geomorphological Changes of River Channel - Jurate Suziedelyte-Visockiene; Arminas Stanionis; Egle Tumeliene; Ruta Puziene (Advances in Civil Engineering)
In Lithuania, the old archival topographic maps of locations of small and medium scale and 1 : 10,000 scale contour photo plans were created on the basis of aerial images. The material of these scales provides documented records on the condition of the objects in the location and the landscape at the moment of aerial photography. Those maps can be used to restore the accurate topographic image of the terrain and buildings in 1945–1951 and in later years and perform the necessary topographic, photogrammetric, and geodetic measurements of the parameters of objects, to identify the location of objects and changes. This information is necessary for a variety of disputed property issues and for building farmhouses in reserves, in areas of forestry land parcels, and for assessment of changes in the landscape. Studies of landscape changes are needed for the assessment of renaturalization processes. This paper presents the geodetic method used for geomorphological changes at the channel of River Žalesa during the period 1942–2017, based on the collected archival cartographic materials: historical topographic maps from archive of the Lithuanian State Company Land Fund, Land Information System, and land management projects and orthophoto maps from Lithuanian spatial information portal and free open-access Sentinel-1 satellite data from the Copernicus Open Access Hub.